Study on the bond properties between steel bar and fiber reinforced concrete after high temperatures. (March 2023) - Li, Xiaodong; Lu, Chengdong; Cui, Yifei; Zhou, Lichen
Abstract: The bond-slip performance between steel bar and normal concrete (NC) and steel fiber reinforced concrete (SFRC) after high temperature were investigated in this paper. The central pull-out test was performed on 40 specimens with specific parameters including the fraction of steel fiber by volume ( Vf  = 0 %, 0.5 %, 1.0 %, and 1.5 %) and temperature ( T  = 20 °C, 200 °C, 400 °C, 600 °C, and 800 °C). The results demonstrate that the bond strength increased with the increase of Vf . The increase in bond strength of SFRC specimens compared to NC specimens is more than 66.9 % after 600 °C. As the temperature increases, the bond strength decreases. The bond strength loss after 600 °C compared to room temperature was more than 46.6 % for SFRC and NC specimens. The synergistic effect of steel fibers and aggregates formed a rigid skeleton for bridging cracks, improving the bond strength between steel bar and SFRC. The cumulative initial damage (interface and thermal cracks) generated by temperature reduced the bond strength. An empirical formula for predicting the bond strength was proposed. The bond stiffness decreased with the increase of temperature and increased with the increase of Vf . SFRC specimens with Vf  = 1.5 % exhibited insignificant changes in bond toughness after high temperature compared to those with Vf  = 1.0 %. The steel fibers significantly improved the bond toughness of SFRC specimens at room temperature. Empirical formulas for predicting bond stiffness and bond toughness were proposed. A prediction model for the bond-slip relationship between steel bar and SFRC after high temperature considering Vf and temperature was proposed. It is found that the established model of the bond-slip relationship agreed well with the experimental results.